CA2-05: Continuous Monitoring and Timely Intervention are Needed to Improve Adherence to Adjuvant Hormonal Therapy Among Breast Cancer Patients - Quinn, Virginia (Marshfield Clinic, 2012)
BACKGROUND/AIMS: There are approximately 150,000 new hormone-sensitive breast cancer cases in the U.S. each year. Numerous studies have shown that adjuvant hormonal therapy (AHT) dramatically reduces breast cancer recurrence and mortality. Daily treatment for 5 years is the recommended therapy among ER+ women. Yet, reports of under-utilization are alarming, ranging from 30% to more than 50%. METHODS: We examined under-utilization of AHT among members of Kaiser Permanente Southern California (KPSC), a nonprofit prepaid managed care organization dedicated to providing evidence-based medicine. KPSC serves 3.3 million socioeconomically diverse members broadly representative of the racial/ethnic groups living in southern California. Subjects were members of the health plan for one or more years and had comprehensive medical and pharmacy benefits. We identified 10,827 women diagnosed with breast cancer between 2000 and 2007 from the health plan’s SEER-affiliated cancer registry who were eligible for AHT. We used automated pharmacy prescription records to describe uptake and utilization of AHT (primarily tamoxifen (Tam) and aromatase inhibitors (AI)) over the 5 years of recommended therapy. RESULTS: In this insured population, we found 14% of eligible breast cancer survivors did not begin AHT (1516/10,827). Of those who started AHT, over 30% had sub-optimal adherence defined as a medication possession ratio <80%. Discontinuation of AHT, defined as greater than 90 days without medication, began in year 1 (7%) and reached 22% and 25% by the end of years 4 and 5, respectively. DISCUSSION: Monitoring and intervention for improving adherence to AHT needs to begin by one year after breast cancer diagnosis and continue across the 5 years of recommended therapy in order to ensure women receive optimal benefit from this lifesaving treatment.